Financial Performance, Debt-to-Equity Ratio, Return on Assets, and Total Asset Turnover on Earnings Per Share and Stock Price as Moderator - Eko Budi Satoto; Masno Marjohan; Suyanto Suyanto (Universitas Mercu Buana, 2023)
Objectives: This paper sought to undertake a comprehensive analysis aimed at investigating the influence arising from the various financial metrics, namely the Current Ratio, Debt-to-Equity Ratio, Return On Assets, and Total Assets Turnover on Earnings Per Share (EPS), and Stock Prices as the moderating variable. Methodology: This research employs a quantitative descriptive methodology by collecting financial reports of Food and Beverage companies listed on the Indonesia Stock Exchange (BEI). The measurement model and hypothesis testing are Descriptive Statistics with a Panel Data Regression Model Selection.Finding: The study found that the Current Ratio had no significant direct effect on Earnings Per Share (EPS), while the Debt to Equity Ratio, Return on Assets, and Total Assets Turnover all had varying degrees of negative influence on EPS via Stock Price. The combined impact of these metrics was statistically significant, emphasizing the importance of considering multiple factors when assessing financial performance.Conclusion: The use of predictive models to forecast stock performance based on these factors can offer significant benefits to both investors and company management. Moreover, this research can aid in the development of better financial metrics, more effective risk management, smarter investment strategies, and an interdisciplinary approach to understanding the complex relationships between financial factors and stock prices. All of this will provide more robust tools for evaluating company performance and making better investment decisions in the world of investments.